Studies on the Spike Disease of Sandal santalum album Linn - Narasimhan, M. J. (Indian Forester, 1954)
Earlier investigators on spike disease of Sandal formulated theories regarding the cause of the disease, such as "unbalanced circulation of sap", and deleterious effect of the host plants on sandal, etc., without adducing sufficient or any experimental data. The infectious nature of the disease was established by us for the first time, by reproducing the spike symptoms on a healthy plant by grafting a small spiked twig on it. Haustorial connections between spiked trees and healthy trees were carefully traced out to infer the possibility of the underground transmission of the disease through the roots. Many methods of sap inoculation to transmit the disease were tried, but were not successful. Some promising methods are yet to be tried. Cytological investigations, carried out in great detail, revealed that in the diseased tissue intracellular inclusions adpressed to the nuclei, were regularly present. These inclusions are characteristic features of some of the plant and animal virus diseases, worked out by other investigators. An article entitled "Cytological investigations on spike disease of sandal" was published by me in Phytopathology.